Desain Reaktor Polimerisasi Prarancangan Pabrik Acrylonitrile Butadiene Styrene (Abs) Dengan Proses Emulsion - Selsa Idillah; Sri Helianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrylonitrile Butadiene Styrene (ABS) is a copolymer composed of polymerization styrene, acrylonitrile, and polybutadiene. Excellent toughness, good dimensional stability, and chemical resistance are ABS properties that are appealing. ABS is regularly used to make lightweight, rigid, and malleable products such as medical devices, cosmetics, household appliances, cabinets, bathtubs, pipes, and vehicle components. Consumption of plastics will continue to increase by 5% per year in Indonesia. Demand for ABS has increased significantly with imports, our final project is proposed to design an ABS plant that meets 10% of domestic ABS needs. Also, the establishment of this factory was based on advancing Indonesia's economic sector and allocates jobs for local labor. The ABS plant construction is going to hold for three years in 2022-2025. It is planned to be located in the Tanjung Buton industrial area, Riau, with a capacity of 115.000 tons/year. This capacity is to meet domestic needs and the Asia market. The ABS Emulsion Process consists of 3 stages; polybutadiene synthesis, the grafting polymerization reaction stage, and the product separation stage. The main design of this paper is polymerization reactor (R-102), which is Continuous Stirred Tank Reactor (CSTR) type. The operating conditions in the reactor were 73 oC and 21.67 psi. Economic analysis is also taken into account to determine whether the factory is feasible. From the economic analysis, we obtained a payback period (PBP) of 1 year, an Internal Rate of Return (IRR) of 22.75%, an Return On Investment (ROI) of 49.45%, and a Break-Even Point (BEP) of 51%, based on the feasibility analysis, it shows that the ABS plant project is feasible. Keywords: acrylonitrile, butadiene, styrene, economic analysis, plant design